Very rapid insight generation to support UK health and care systems: An AHSN approach - Chandler, Jackie; Darnton, Philippa; Sibley, Andrew (Frontiers in Sociology, 2023)
NHS Covid-19 challenges are well documented. Academic Health Science Networks (AHSNs) are a key partner to NHS organizations. Wessex AHSN’s Evaluation team responded by offering rapid insight generation and evaluation to local NHS systems to capture learning from managing Covid-19 challenges. This novel ‘Rapid Insight’ approach enabled multiple parts of local systems to collectively learn in a rapidly changing pandemic environment. Key objectives were to enable systems and leaders to build their adaptive leadership capability (Heifetz, 1994, Liles and Darnton, 2020) and learn from the experience of Covid-19 to inform both recovery planning and Wessex AHSN’s support. Rapid Insight (RI) developed to gain knowledge quickly through remote systems. Key healthcare professionals gathered into a tightly managed, virtual forum to share system intelligence. Focused questions asked about the systems response to the pandemic, what changes to continue and sustain, or discontinue. Participants responded simultaneously to each question using the virtual chat function. Immediate thematic analysis of the chat was conducted in 48-72 hours by paired analysts for each question to strengthen analytical integrity. Due to restricted time, mind maps, the key output, showed linkages between themes. Telephone or virtual interviews of key informants (healthcare professionals and patients) and routinely collected data were synthesized into short reports alongside some RI events. However participant recruitment, due to insufficient time, was not able to engage with certain groups of people (e.g., mental health users). Data obtained can scope the problem and immediate system needs, to stimulate questions for future evaluative work. Increased participation of less heard voices, a key benefit, allowed greater diversity of experience. RI also facilitated a shared endeavor to discover “clues in the system.” Although, these rapid virtual events saved on travel time, digital exclusion might constrain participation for some stakeholders which will need other ways to ensure inclusion. Successful rapid engagement required AHSN’s existing system relationships to champion RI and facilitate participant recruitment. RI events ‘opened the door’ to conversations between up to one hundred multi-professional clinicians to share their collective response to Covid-19. This paper focusses on the RI approach with a case example and considers its further development.